PENERAPAN STANDAR AKUNTANSI BERBASIS AKRUAL PADA PENYUSUNAN LAPORAN KEUANGAN DI PEMERINTAH DAERAH KABUPATEN ENREKANG - Tarawiru, Yasri (Economos : Jurnal Ekonomi dan Bisnis, 2020)
This study aims to determine the Application of Accrual Based Accounting Standards in the Compilation of Financial Statements in Enrekang District Government and to determine the factors that influence in the Implementation of Accrual Based Accounting Standards in the Compilation of Financial Statements in Enrekang District Government. The research method used in this research is a descriptive qualitative method. The results show that the application of accrual-based accounting standards in the preparation of financial reports has been implemented but in 2016 has not been fully implemented and in 2017 has been fully implemented following Government Regulation No. 71 of 2010 concerning the Application of Government Accounting Standards. The factors that influence the Application of Accrual Based Accounting Standards in the Compilation of Financial Statements in Enrekang District Government namely Human Resources (HR) and Facilities and Target are both very influential in the preparation of financial statements.